Peran Penting Promosi Kesehatan dalam Pencegahan Penyakit Kronik - Nur Arifatus Sholihah; Fitriah Fitriah; Andi Ilham; Leni prawitasari; Rudy Kurniawan; Neneng Prihasti; Safriandi Safriandi; Fitrini Fitrini; Dewi Indiastuti (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Chronic diseases are degenerative conditions that significantly impact an individual's quality of life. Various degenerative diseases, such as diabetes mellitus, hypertension, and heart stroke, require immediate attention. Indonesia faces a dual burden in healthcare, grappling with both rampant infectious diseases and the rising prevalence of chronic degenerative illnesses. Therefore, health promotion efforts are crucial in preventing degenerative diseases among adolescents. This initiative targets teenagers due to their unhealthy lifestyle choices, which are evident in their smoking habits, poor dietary practices, insufficient consumption of fruits and vegetables, and a lack of physical activity. The primary objective of this initiative is to enhance awareness regarding the prevention of degenerative diseases among youth and to address the emergence of such conditions in this age group. The results of the community service activities indicate a notable increase in average knowledge from 6.61 to 13.80 and an improvement in attitudes from 9.61 to 14.47. The community service activities were successfully executed, as evidenced by the smooth conduct of the events and the active participation of the adolescents. To improve health quality, it is essential to foster awareness and enhance education among teenagers about the prevention of degenerative diseases.